HOW TO INCREASE EMPLOYEE SATISFACTION IN THE BANKING SECTOR - Noermijati, Noermijati; Firdaus, Ema Zahra; Taufiqurrahman, Taufiqurrahman (Universitas Brawijaya, Indonesia, 2022)
This study was conducted to determine the mediating role of job burnout and the moderating role of equity compensation on the effect of job demand on employee satisfaction. The study was conducted on 131 employees of Bank X in Malang by using Partial Least Square (PLS) analysis. The results showed that job demand had a significant direct effect on job burnout and employee satisfaction, while job burnout had no impact. On the other hand, job burnout does not play a mediating role, and equity compensation does not play a role in moderating the effect of job demand on employee satisfaction. This study places job burnout as a mediating variable and equity compensation as a moderating variable on the effect of job demand on employee satisfaction. An essential finding of this study is that the hypothesized mediating and moderating roles were not proven. It is necessary to pay special attention to the job demand/ demands imposed on employees to affect employee satisfaction positively. Physical demand is something that needs to be considered. When employees feel burdened and unable to meet the given physical demands, employees may experience job burnout which is indicated by the loss of enthusiasm from employees at work.